The Use of Alternative Assessment (Observation) and Student Learning Outcomes In English Classrooms: How Do They Correlate? - Elin Restiani Sunandang; Yayu Heryatun; Anita Anita (Scope : Journal of English Language Teaching, 2023)
Using alternative assessments such as observation is one of the various types of evaluation that teachers can apply during the learning process. Each teacher is expected to monitor students while they are studying English in primary schools. This study aims to determine whether there is a relationship between the uses of observation assessments with student learning outcomes. This research focused on 31 fourth graders enrolled in an Islamic elementary school. This research was a correlational study using the observation of evaluation of learning outcomes of alternative English topics for students. In this research, SPSS 25th Version was used to determine the validity or effect. Based on the calculation results, the r count is 0.820 according to the t table with a 5% significance criterion of 0.355; thus, Ha is allowed because r arithmetic is more significant than the r table. According to the research findings, using alternative evaluations in observation substantially give an impact for the academic results of elementary school students in English courses.